Evaluación del punto de congelamiento de las mezclas entre jet fuel A-1 con biocombustibles y aditivos (2021)
The research work presents a proposal for a competitive aeronautical fuel in price and performance, made in Colombia, that complies with the ASTM D-1655 standard, implementing a mixture between jet fuel, three different types of biofuels produced in the country and two kinds of ice inhibitor additives, based on a one-factor and one-block experimental design consisting of four different concentrations of biofuels and a maximum concentration of antifreeze governed by the ASTM. Similarly, blends without antifreeze assistance were carried out under the same biofuel concentrations and blends of biofuel with fuel alcohol as antifreeze, all carried out with the 4 concentrations stipulated and without the presence of the additive.